Young Adults’ Online and In-Person Sexual Harassment Experiences in Romantic Relationships: Exploring the Role of Relationship Type and Dark Triad Personality Traits - Schokkenbroek, Janneke M. (International criminal justice review, 2024)
As romantic relationships in young adulthood (18–25 years) are frequently characterized by experimentation and risk-taking, this could make young adults particularly vulnerable to experience sexual harassment by a dating or committed partner. This study examines young adults’ victimization and perpetration experiences of online and in-person sexual harassment with their dating or committed partner, and explores the role of the Dark Triad personality traits. We conducted a cross-sectional survey among 458 young adults, 371 of whom were in a romantic relationship (Mage = 20.80, SDage = 1.51, 25.6% men). Our findings revealed that all measured sexual harassment experiences were significantly more prevalent among young adults in dating relationships compared to those in committed relationships. Furthermore, in both relationship types, all online and in-person experiences of sexual harassment were significantly linked, indicating that these harmful experiences occur across contexts. Additionally, all victimization and perpetration experiences were significantly linked in both relationship types, meaning that some young adults were both victims and perpetrators of these behaviors. Lastly, we found that sexual harassment was linked to narcissism in dating relationships, but to Machiavellianism in committed relationships, indicating that different strategies may explain these behaviors.